Lamella Structure of Zinc Aluminum Layered Double Hydroxide as Molecular Containers for the Preparation of Mesoporous Carbon - Lim, Sheau Wen (2006)
Open lamella systems such as layered double hydroxides (LDHs) can be used to generate new nanostructured materials of layered organic-inorganic nanohybrid type. The inorganic Zn-Al-layered double hydroxide (ZAL) was used as a matrix, hosting an active agent or a guest, toluene-4-sulphonate (TSA), 2,4-dichlorophenoxyacetic acids (24D), naphthaleneacetic acid (NAA) anthraquinone-2,6-disulphonate (AQDS) and dodecylsulfate sodium salt (SDS). They were prepared by spontaneous self-assembly method from an aqueous solution for the formation of a new layered organic-inorganic hybrid nanocomposite material. The Zn to Al ratio at R=4 and the various concentrations of anion organics at pH 10 was found suitable to give well-ordered nanolayered organic-inorganic hybrid structure. PXRD and FTIR analyses show that the inorganic-organic structure of LDH expanded from 8.8 Å to accommodate the anion organics for the formation of the nanocomposite. Nanocomposites were then calcined under N2 gas at different temperatures, 500 °C, 700 °C, and 1000 °C for the formation of the carbon products. In order to remove the carbonaceous products from the template matrix, the carbonized nanocomposite was treated with 2 M nitric acid. Powder X-ray diffraction pattern of the carbons showed that they are of amorphous type. The surface area and porosity studies show that the resulting materials are of mesoporous carbon with high BET surface area and high percentage of micropore content. No significant difference in the surface morphology of ZAL and its nanocomposites was observed under a scanning electron microscope. Both of them afforded non-uniform irregular agglomerates of compact and non-porous structure of plate-like morphology. The morphology of carbons showed agglomerates of compact and porous granular structure.